Improvement of photovoltaic performance and stability of AnE-PV:PCBM based organic solar cells using solution processed inverted geometry - Yuksel, Sureyya Aydin; Ongul, Fatih; Bozar, Sinem; Varal, Nurhan Mehmet; Kus, Mahmut; Cakmak, Gulbeden; Guney, Hasan Yuksel; Egbe, Daniel Ayuk Mbi; Gunes, Serap (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Organic bulk heterojunction and inverted type solar cells were fabricated using AnE-PVstat:PCBM blends as photoactive layers. The device was inverted using thin films of TiO2 as hole blocking and electron conducting layers. The power conversion efficiency (PCE) of organic bulk heterojunction solar cells increased from 1.70% to 2.59% when inverted device configuration was used instead of regular organic bulk heterojunction solar cell configuration. Stability studies reveal that the inverted type devices are more stable than the herein investigated regular organic bulk heterojunction solar cells fabricated using AnE-PVstat:PCBM blends as photoactive layers. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: AnE-PVstat; TiO2; Inverted type solar cells; Different top electrodes; TITANIUM-OXIDE; EFFICIENT; ELECTRON; LAYER; ENCAPSULATION; Materials Science; Physics